2005
DOI: 10.1152/ajpheart.00673.2004
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metaboreflex modulates the arterial baroreflex dynamic effects on peripheral vascular conductance in humans

Abstract: by the ultrasound Doppler method), leg vascular conductance (LVC), mean arterial blood pressure (MAP), and heart rate (HR)] in humans. In 12 healthy subjects (10 men and 2 women), who performed sustained 1-min handgrip exercise at 50% maximal voluntary contraction followed immediately by an imposed postexercise muscle ischemia (PEMI), 5-s periods of neck pressure (NP; 50 mmHg) or neck suction (NS; Ϫ60 mmHg) were used to evaluate carotid baroreflex function both at rest (Con) and during PEMI. First, the decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
4
26
1
1
Order By: Relevance
“…Indeed, this association suggests that MSNA and the magnitude of the ensuing sympathetic vascular transduction importantly contribute to the support of resting BP. In agreement, a nearly identical time line has been found for increases in MSNA and subsequent alterations in vascular tone and BP during carotid baroreceptor perturbation (13,22). Importantly, we also found that cardiac cycles without MSNA bursts (nonbursts) are followed by a subsequent increase in LVC and decrease in BP.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, this association suggests that MSNA and the magnitude of the ensuing sympathetic vascular transduction importantly contribute to the support of resting BP. In agreement, a nearly identical time line has been found for increases in MSNA and subsequent alterations in vascular tone and BP during carotid baroreceptor perturbation (13,22). Importantly, we also found that cardiac cycles without MSNA bursts (nonbursts) are followed by a subsequent increase in LVC and decrease in BP.…”
Section: Discussionsupporting
confidence: 90%
“…CO and LBF were measured using Doppler ultrasound as previously described in detail (22,23,43). Briefly, a Doppler ultrasound system (HDI 3500, Philips) equipped with a hand-held transducer probe (model D2 CW) with an operating frequency of 2 MHz was used to measure aortic blood velocity in the suprasternal notch.…”
Section: Subjectsmentioning
confidence: 99%
“…The box pressure was measured using a pressure transducer mounted on the box. We measured exercising LBF using Doppler ultrasound, as previously described (20,48). Briefly, a Doppler ultrasound system (HDI 5000; ATL Ultrasound, Bothell, WA) equipped with a hand-held transducer probe (model L12-5) with an operating frequency of 6 MHz was utilized to simultaneously measure two-dimensional common femoral artery diameter and mean blood velocity (MBV).…”
Section: Methodsmentioning
confidence: 99%
“…The crosssectional area of the femoral artery (CSA) was estimated using a representative Dm as CSA ϭ (Dm/10/2) 2 ·. MBV was continuously estimated using a computer program developed with the aid of LabVIEW (version 6.0; National Instruments), as described in detail elsewhere (20). Our system collects MBV at 100 Hz together with the analog signals representing the ECG, blood pressure waveform, and box pressure.…”
Section: Methodsmentioning
confidence: 99%